Mulheres integralistas e o mito da passividade feminina: Nilza Perez e o “feminismo verde” (1932-1937) - Manfrinatti, Mariana Machado (2023)
The dissertation analyzed the standard of "being a woman" set by the Brazilian Integralist Action for its militants, through the 1949 book "A Mulher no Século XX" (Woman in the 20th Century) by leader Plínio Salgado and the magazine "Anauê!" (Anauê!). However, by understanding what was expected and demanded of women, both the magazine "Anauê!" and "Brasil Feminino" and an interview with the daughter of the former militant, Nair Nilza Perez, allowed us to find some ruptures in the limits determined by the Integralist ideology. In this way, the stereotypes of complete submission found in historiography in relation to conservative/right-wing women were questioned and analyzed from the perspective of gender studies. The green blouses claimed to possess true feminism and constituted speeches that diverged from integralist ideals. Thus, by questioning traditional historiography and the writing of history that limits and/or silences women - here directly integralist women - it allowed us to break with the myth of passivity that is imposed on them.